2006
DOI: 10.1088/0957-4484/17/14/011
|View full text |Cite
|
Sign up to set email alerts
|

Relation between conduction property and work function of contact metal in carbon nanotube field-effect transistors

Abstract: We have investigated the relation between the conduction property and the work function of the contact metal in carbon nanotube field-effect transistors (NTFETs). The conduction type and the drain current are dependent on the work function. In contrast to NTFETs with Ti and Pd contact electrodes, which showed p-type conduction behaviour, devices with Mg contact electrodes showed ambipolar characteristics and most of the devices with Ca contact electrodes showed n-type conduction behaviour. This indicates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 22 publications
3
112
0
Order By: Relevance
“…73,91 Nosho et al used Pd, Ti, Mg, and Ca to contact CNTs and observed an increase in the on-state current of the hole branch of the transfer characteristics with increasing metal work function. 92 However, Ca contacts for which a zero Schottky barrier height for electrons is expected, due to the low Ca work function of 2.9 eV, exhibited an electron current lower than expected. This indicates that either the work function of the Ca contact is far from that of a clean surface in vacuum, there is an oxide at the metal-CNT interface or there are additional tunneling barriers limiting the current.…”
Section: A Measurements Of Schottky Barrier Heightsmentioning
confidence: 89%
“…73,91 Nosho et al used Pd, Ti, Mg, and Ca to contact CNTs and observed an increase in the on-state current of the hole branch of the transfer characteristics with increasing metal work function. 92 However, Ca contacts for which a zero Schottky barrier height for electrons is expected, due to the low Ca work function of 2.9 eV, exhibited an electron current lower than expected. This indicates that either the work function of the Ca contact is far from that of a clean surface in vacuum, there is an oxide at the metal-CNT interface or there are additional tunneling barriers limiting the current.…”
Section: A Measurements Of Schottky Barrier Heightsmentioning
confidence: 89%
“…Even though the diode itself is not a main element of modern digital electronics, the physics of the diode structure is essential for many applications, including in optoelectronics [3]. Nanoscale diodes have been already demonstrated with carbon-based nanomaterials, such as graphene and individual nanotubes [4][5][6][7][8][9][10][11][12][13][14]. The work presented here focuses on diode structures made of parallel nanotube arrays, their rectification properties, and the physics of their electronic transport.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodes defined by photolithography and liftoff were deposited directly on the arrays. One electrode was Pd(30 nm)/Ti(1 nm), providing the Ohmic contact [22][23][24] and the other electrode was Al(30 nm)/Ca(3 nm), providing the Schottky contact [9,25] to the s-SWNTs. Since the thickness of the deposited Ti layer was smaller than a typical SWNT diameter, the SWNTs had actual contacts to the Pd-bulk with the work function ~5.1 eV [22][23][24], making p-contacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the semiconducting carbon nanotube Schottky diodes is much dependent on the Schottky barrier height built in the metallic-semiconducting carbon nanotube contacts. This barrier height depends on various material parameters, for example: the metal contact work function, the environment to which the device is exposed, the diameter of the nanotube and the interface structures [11][12][13][14][15][16]. Constantly advancement of the semiconducting carbon nanotube Schottky diode performance requires a good understanding of the metallic-semiconducting carbon nanotube contacts.…”
Section: Introductionmentioning
confidence: 99%